3D microcalcification detection using a color Doppler twinkling artifact with optimized transmit conditions: Preliminary results. Issue 12 (19th October 2020) - Kang, Jinbum; Han, Kanghee; Kim, Kang‐Sik; Jang, Won Seuk; Kim, Min Jung; Yoo, Yangmo
Abstract : Purpose: Mammography is the only method that has been proven to detect breast microcalcifications (MCs), but the sensitivity of mammography varies according to breast density. This paper proposes an ultrasound (US) color Doppler twinkling artifact (CDTA) method with optimized transmit conditions to identify breast MCs without ionizing radiation. Methods: The transmit conditions for US color Doppler imaging (CDI) were optimized to enhance the sensitivity of the twinkling artifact (TA) that arises from random scattering on rough surfaces of breast MCs. To validate the proposed breast MC detection method, a chicken breast phantom with MC particles (groups of particles <400  μ m and <240  μ m ) was fabricated and scanned by a digital mammography system and an US research platform by an L11‐5v linear array probe with a three‐dimensional (3D) motion tracking system. Results: From the phantom experiment, the proposed 3D CDTA imaging method with optimized transmit conditions (i.e., a center frequency of 5.0 MHz, an f‐number of 1.3, and a peak negative pressure of 1.83 MPa) successfully detected all 16 MC particles, comparable to detection with mammography. For a human breast surgical specimen in the ex vivo study, all 10 MC clusters, marked by a radiologist on the mammogram, were identified with the proposed 3D CDTA imaging method. Conclusions: In the phantom and ex vivo breast specimen studies, the proposed 3D CDTA imaging method successfully detected MCs, and the spatial localization was highly correlated with the mammogram results. These results indicate that the proposed 3D CDTA imaging method has great potential for the detection of MCs without ionizing radiation.